Chapter 9: Amperometric ion sensing approaches at liquid/liquid interfaces for inorganic, organic and biological ions - Lee, H.; Arrigan, Damien; Karim, M.; Kim, H. (2016)
Electrochemistry at the interface between two immiscible electrolyte solutions (ITIES) has become an invaluable tool for the selective and sensitive detection of cationic and anionic species, including charged drug molecules and proteins. In addition, neutral molecules can also be detected at the ITIES via enzymatic reactions. This chapter highlights recent developments towards creating a wide spectrum of sensing platforms involving ion transfer across the ITIES. As well as outlining the basic principles needed for performing these sensing applications, the development of ITIES-based detection strategies for inorganic, organic, and biological ions is discussed.